A very short, fairly interesting and reasonably cheap book about knowledge management - Roberts, Joanne (Los Angeles : SAGE, 2015)
This concise introduction to knowledge management and its current place in and implications for contemporary management theory and practice explores what knowledge management is, why it is significant, and where it is going.
Introduction: The rise of knowledge management -- Situating knowledge management -- Knowledge management? -- Knowledge acquisition, retention, and transfer -- Knowledge, creativity, and innovation -- Ignorance, forgetting, and unlearning -- Conclusion: Looking forward.
Includes bibliographical references (pages 131-145) and index.
Description based on MARC record for print version.
Keywords: Knowledge management